PENGARUH MODEL STORYTELLING TERHADAP KETERAMPILAN BERCERITA BERBANTU MEDIA WAYANG NUSANTARA PADA MATA PELAJARAN BAHASA INDONESIA KELAS V SD 2 KALIWUNGU - Rohmini, Siti Luvikasari; Dhina Cahya Rohim; Devy Aufia Abshor; Amalia Rahmawati; Deki Wibowo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to determine the effect of learning models storytelling using Indonesian wayang media for storytelling skills in class V of SD 2 Kaliwungu. This type of research is Quantitative with a Quasi-Experimental Pretest-Posttest Design, with research subjects of class V students at SD 2 Kaliwungu, totaling 40 students. The data collection techniques used in this research were tests, observation, interviews, and student response questionnaires. Based on the Normality test, results pretest-posttest the experimental class shows a significance value of 0.244 and the results pretest-posttest the control class shows a significance figure of 0.078, so it can be concluded that the data is normally distributed. Based on the Paired sample T-test analysis, it is known that the Sig (2-tailed) value is 0.001 due to the sig value. (2-tailed) is less than 0.05, so it can be concluded that the learning model storytelling Using Indonesian wayang media has an effect on the storytelling skills of class V students at SD 2 Kaliwungu.